Research and Optimization of Hybrid On-Board Energy Storage System of an Electric Locomotive for Quarry Rail Transport - Goolak, Sergey; Kondratieva, Liliia; Riabov, Ievgen; Lukoševicius, Vaidas; Keršys, Arturas; Makaras, Rolandas (My University, 2023)
Operation modes of rolling stock at mining enterprises are considered and analyzed. The justification of the need to replace it with a modern specialized electric locomotive for quarry railway transport, equipped with an asynchronous traction electric drive and an on-board energy storage system, is presented. The determination of the parameters and structure of the on-board energy storage system, based on the condition of power compensation with limited power consumption from the traction network and ensuring the autonomous movement of the electric locomotive, is considered. This study was carried out by modeling the processes of energy exchange in the traction system of an electric locomotive. The use of lithium cells and supercapacitors in energy storage is considered. Variants of the hybridization of energy storage were studied from the standpoint of minimizing the weight, size, and cost indicators. It was established that reducing the mass of the energy storage device, which includes lithium cells and supercapacitors, leads to an increase in the cost of one kilowatt-hour of energy storage capacity, which reduces the attractiveness of capital expenditures for the creation of such an energy storage device. Hybridization of the energy storage device by combining lithium cells of different types practically does not improve its weight, size, and cost indicators. The recommended option is a storage capacity of energy based on LTO elements, for which it is necessary to select elements in order to minimize weight, size, and cost indicators.
Keywords: quarry railway transport; electric locomotive; on-board energy storage system; traction drive; induction motor